PENGARUH RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), PRICE TO EARNING RATIO (PER), DEBT TO EQUITY RATIO (DER), DAN OPERATING PROFIT MARGIN (OPM) TERHADAP HARGA SAHAM (STUDI PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIOD - Yusrizal Yusrizal; Juneris Juneris (Bilancia : Jurnal Ilmiah Akuntansi, 2018)
This study aimed to examinethe influence of Return On Equity, Earning Per Share, Price to Earning Ratio, Debt to Equity Ratio, and Operating Profit Margin to the Stock Pricein the period 2012-2016. Population and sample in this study are all mining company listed on the Stock Exchange in the year 2012 to 2016. Samples were taken using purposive sampling, in order to get 10 companies in the sample. of Return On Equity, Earning Per Share, Price to Earning Ratio, Debt to Equity Ratio, and Operating Profit Margin to the Stock Price examined using multiple regression analysis. And after tested with SPSS version 19.0 the results obtained is one hypothesis is accepted. On significant t test result that the Earning Per Share variables that significantly influence the Stock Price, where as other variables did not significantly influence the stock price. This showsthat Earning Per Share the only variable that can affect the Stock Price, while variablereturn on equity, price to earning ratio, debt to equity ration and operating profit margindo nothave a huge effec tin mining companieslistedon the Stock Exchange in the year2012 to 2016. Penelitian ini bertujuan untuk melihat pengaruh Return On Equity, Earning Per Share, Price to Earning Ratio, Debt to Equity Ratio dan Operating Profit Margin terhadap harga saham pada periode tahun 2012 – 2016. Populasi dan sampel pada penelitian ini adalah seluruh perusahaan pertambanganyang listing pada di BEI pada tahun 2012 – 2016. Sampel diambil menggunakan purposive sampling, sehingga didapat 10 perusahaan sebagai sampel diteliti. Return On Equity, Earning Per Share, Price to Earning Ratio, Debt to Equity Ratio dan Operating Profit Margin terhadap harga saham menggunakan metode analisis regresi berganda. Dan setelah diuji dengan SPSS versi 19.0 maka hasil yang diperoleh adalah ada satu hipotesis yang diterima. Pada pengujian signifikan t diperoleh hasil bahwa variabel Earning Per Share yang berpengaruh signifikan terhadap harga saham, sedangkan variabel lainnya tidak berpengaruh signifikan terhadap harga saham.Hal ini menunjukkan bahwa hanya variabel Earning Per Share yang dapat mempengaruhi harga saham, sedangkan variabel Return On Equity, Price to Earning Ratio, Debt to Equity Ratio dan Operating Profit Margin tidak memiliki pengaruh yang besar pada perusahaan pertambangan yang terdaftar di BEI pada tahun 2012 – 2016.